A temperature-responsive release cellulose-based microcapsule loaded with chlorpyrifos for sustainable pest control - Xiao, Douxin; Liang, Wenlong; Xie, Zhengang; Cheng, Jingli; Du, Yongjun; Zhao, Jinhao (Journal of hazardous materials, 2021)
[Display omitted] •A temperature-responsive microcapsule loaded chlorpyrifos (CM@CPF) was constructed.•The release process is controlled by the phase transition of hexadecane in the core.•The control efficacy of CPF@CM against P. xylostella was correlated with temperature.•CM@CPF showed a higher adhesion ability on cucumber and peanut leaves.•CM@CPF could enhance the light stability and biosecurity of CPF technical. Controlled pesticide release in response to environmental stimuli by encapsulating pesticide in carrier is a feasible approach to improve the effective utilization rate. Here, a temperature-responsive release microcapsule loaded with chlorpyrifos (CPF@CM) was prepared from n-hexadecane-in-water emulsions via interfacial polymerization. The microcapsule was consisted of nanofibrillated cellulose (NFC) as the shell wall material and isophorone diisocyanate (IPDI) as the crosslinker. The prepared CPF@CM had pesticide-loading efficiency (33.1 wt%) and favorable adhesion on the surface of cucumber and peanut foliage compared with conventional formulation. Additionally, CPF@CM could protect chlorpyrifos against photodegradation effectively. The in vitro release test showed that microcapsule had adjustable controlled-release characteristics with the change in temperature based on phase transition of the n-hexadecane core. Bioassay studies showed that control efficacy of CPF@CM microcapsule against P. xylostella was positively correlated with temperature because of temperature-induced changes in release rate. The acute toxicity of CPF@CM to zebrafish was reduced more than 5-fold compared with that of CPF technical. These results indicated that the microcapsule release system has great potential in the development of an effective and environmentally friendly pesticide formulation.